The use of mobile technologies for Web 2.0 based service delivery to graduate students in Ghanaian Universities : the case of the University for Development Studies (UDS), Ghana. - Holmner, Marlene Amanda (University of Pretoria, 2015)
Mini Dissertation (MIT)--University of Pretoria, 2014.